HUBUNGAN ANTARA BERAT TAS DENGAN NYERI PUNGGUNG ANAK SEKOLAH USIA 6 - 13 TAHUN : Literature Review - Syifa Bakhitah, (2021)
Background: Continuous use of bags weighing >10% of body weight in school children will cause musculoskeletal complaints, one of which is back pain. Therefore, this paper aims to analyze the relationship between bag weight and back pain which was reviewed through journals that have been found. Method: The writing used is a literature review and the journal used is a type of research Cross Sectional. Search literature this was obtained through published internet sites, such as Google Scholar and PubMed. The methodological quality assessment of the 4 journals was assessed with the Scimago Journal and Country Rank (SJR). The literature review used is published in the last 5 years 2016-2021. The criteria for the journals reviewed are international journals that use English with the subjects of school children aged 6-13 years using school bags with a load of >10% body weight, male and female. Results: After reviewing the literature on 4 journals, it showed that there was a significant relationship between bag weight and back pain for school children aged 6-13 years. Conclusion: Significant weight of bag with back pain in school children aged 6-13 years. Keywords : bag weight, back pain, school children